Influencing Factors Regarding the Severity of Peri-Implantitis and Peri-Implant Mucositis - Csilla Benedek; Bernadette Kerekes-Máthé; Liana Bereșescu; Imola Zsuzsa Buka; Zsuzsanna Bardocz-Veres; Ildikó Geréb; Krisztina Ildikó Mártha; Kinga Mária Jánosi (Diagnostics, 2024)
The scientific literature is increasingly focused on peri-implant mucositis and peri-implantitis, which are biological outcomes of dental implant treatment. Background/Objectives: The present study aimed to evaluate the two most critical complications of dental implantation, peri-implant mucositis and peri-implantitis, through the prism of different influencing factors. Methods: We followed 40 patients, with a total number of 92 dental implants, divided into three age groups: under 35 years, between 35 and 55 years, and older than 55 years. Patients were also divided into groups according to the time since implant placement: 1–3 years, 4–7 years, and more than 7 years. The patients were examined, and periodontal pocket depth, peri-implant pocket depth, Löe–Silness gingival index, mucosal thickness, and keratinized mucosal width were recorded; bone resorption was measured on radiographs using a 2D image analysis method; and a questionnaire was also conducted. Results: Bone resorption was highest in the 35–55 age group (3.09 ± 0.04 mm) and for implants placed 4–7 years ago (3.39 ± 0.12 mm). Females had a mean bone resorption of 3.4 ± 0.15 mm and males of 2.45 ± 0.07 mm. Statistically, there was a significant difference only in the Löe–Silness index: the 35–55 age group had the highest values (p = 0.04). Conclusions: There were no statistically significant differences between the time since implant placement and the degree of bone resorption, nor between sexes. Peri-implant inflammation may occur at any age, regardless of the lifetime of the implants.